2011
DOI: 10.1158/0008-5472.can-11-1637
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Targeting Hampers Prostate Adenocarcinoma Development but Promotes the Occurrence of Highly Malignant Neuroendocrine Cancers

Abstract: Mast cells (MC) are c-Kit-expressing cells, best known for their primary involvement in allergic reactions, but recently reappraised as important players in either cancer promotion or inhibition. Here, we assessed the role of MCs in prostate tumor development. In prostate tumors from both tumor-prone transgenic adenocarcinoma of the mouse prostate (TRAMP) mice and human patients, MCs are specifically enriched and degranulated in areas of well-differentiated (WD) adenocarcinoma but not around poorly differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 46 publications
11
123
0
Order By: Relevance
“…In our study we observed a similar relationship with microvessel MC density, while the relationship between MCs and tumor grade was inverse and very weak. The inverse correlation between Gleason score and MC density could be expected from other studies [18,19], while others reported results similar to Stawerski et al [20].…”
Section: Discussionsupporting
confidence: 79%
“…In our study we observed a similar relationship with microvessel MC density, while the relationship between MCs and tumor grade was inverse and very weak. The inverse correlation between Gleason score and MC density could be expected from other studies [18,19], while others reported results similar to Stawerski et al [20].…”
Section: Discussionsupporting
confidence: 79%
“…27). MC distribution and frequency in colon were assessed by toluidine blue stain, as previously reported (28). MCs were counted in five nonoverlapping high-power microscopic fields (Â400) and results were expressed as means.…”
Section: Histology and Ihcmentioning
confidence: 99%
“…In the context of the TME, mast cells are recognized as an early and persistent infiltrating cell type involved in angiogenesis, tissue remodeling, and immune modulation (9). Mast cells may have both antitumor and tumor-promoting roles, potentially also in the same context (10,11).…”
Section: Introductionmentioning
confidence: 99%